Protective oral vaccination against infectious salmon anaemia virus in Salmo salar. (July 2016) - Caruffo, Mario; Maturana, Carlos; Kambalapally, Swetha; Larenas, Julio; Tobar, Jaime A.
Abstract: Infectious salmon anemia (ISA) is a systemic disease caused by an orthomyxovirus, which has a significant economic impact on the production of Atlantic salmon ( Salmo salar ). Currently, there are several commercial ISA vaccines available, however, those products are applied through injection, causing stress in the fish and leaving them susceptible to infectious diseases due to the injection process and associated handling. In this study, we evaluated an oral vaccine against ISA containing a recombinant viral hemagglutinin-esterase and a fusion protein as antigens. Our findings indicated that oral vaccination is able to protect Atlantic salmon against challenge with a high-virulence Chilean isolate. The oral vaccination was also correlated with the induction of IgM-specific antibodies. On the other hand, the vaccine was unable to modulate expression of the antiviral related gene Mx, showing the importance of the humoral response to the disease survival. This study provides new insights into fish protection and immune response induced by an oral vaccine against ISA, but also promises future development of preventive solutions or validation of the current existing therapies. Highlights: Oral delivery encapsulated vaccine against ISA in Salmo salar was evaluated. Specific IgM induction, antiviral Mx gene expression and challenge with a highly virulent isolate was measured. Efficacy analysis also include parameters of evidence-based medicine as ARR and NNT. Oral delivery ISA vaccine induced statistically significant protection against a highly virulent ISAV challenge.